Professional Autonomy of High School Teachers in Turkey: A Retrospective and Prospective Policy Analysis - Canbolat, Yusuf (Egitim ve Bilim, 2020)
Unlike the restrictions on teacher autonomy over the decades, recent policy documents developed by the Ministry of National Education propose expanding their professional autonomy in Turkey. Based on existing and potential policies on the agenda, the current study examines high school teachers` professional autonomy in Turkey utilizing explanatory mixed research design.  In the quantitative phase, data were collected from 12.329 teachers sampled via a two-stage stratified sample design by statistical region, school type and subjects using the “Teacher autonomy scale”. Besides, to reveal an in-depth interpretation of the findings obtained in the quantitative dimension, the qualitative dimension was conducted with 12 teachers sampled through the maximum variation method. The qualitative data were collected through a semi-structured interview form developed by the researcher based on findings from the quantitative phase. Results indicate that teachers think all dimensions of professional autonomy are perfectly or very reasonable. They find existing and potential policies of instructional, administrative, and personal-professional development autonomy very feasible whereas they find financial autonomy partly feasible. Although teachers have limited instructional autonomy, their responsibilities for the outcomes of instructional decisions are limited as well, due to the lack of a systematic accountability policy. I argue that potential policies should focus on redress the balance. Based on centrally developed curriculum frameworks, these policies should support teachers` instructional autonomy and increase their responsibility for instructional decisions. Flexible and balanced accountability policies are recommended rather than standardized and test-based approaches. Türkiye’de öğretmenlerin mesleki özerkliği uzun yıllardır sınırlı olmakla birlikte son dönemde Millî Eğitim Bakanlığı tarafından geliştirilen birçok üst politika belgesinde öğretmen özerkliğinin geliştirilmesi hedeflenmektedir. Var olan ve olası politikalar temelinde Türkiye’de genel ortaöğretim düzeyinde öğretmen özerkliğini öğretmen görüşleri aracılığıyla çözümlemeyi amaçlayan bu araştırmada karma araştırma desenlerinden açımlayıcı sıralı desen kullanılmıştır. Araştırmanın nicel boyutunda veriler aşamalı tabakalı yöntemle farklı bölge, okul türü ve branştan 12.329 öğretmenden, “Öğretmen özerklik ölçeği” ile toplanmıştır. Nicel bulgulara ait derinlemesine bilgi elde etmek amacıyla maksimum çeşitlilik örnekleme yöntemiyle farklı bölge, okul türü ve branştan 12 öğretmen ile araştırmacı tarafından geliştirilen yarı yapılandırılmış görüşme formu aracılığıyla nitel veriler toplanmıştır. Araştırma sonucunda öğretmenlerin öğretmen politikaları ile ilişkili; mesleki özerkliğin bütün boyutlarını büyük ölçüde veya tamamen benimsediği bulgusuna erişilmiştir. Öğretimsel özerklik, yönetsel özerklik, kişisel ve mesleki gelişim özerkliği boyutlarına ilişkin var olan ve olası politikalar büyük ölçüde uygulanabilir bulunmakta iken mali özerklik boyutu orta derecede uygulanabilir bulunmaktadır. Öğretmenlerin öğretimsel özerkliği sınırlı olmakla birlikte bu sınırlı alanda aldıkları kararların etkileri konusundaki sorumlulukları da sınırlıdır.  Öğretmenlerin özerklik ve sorumlulukları arasında her ikisini de olumlu yönde geliştirecek bir denge sağlanması gerekmektedir. Merkezi düzeyde geliştirilen çerçeve öğretim programları doğrultusunda, öğretmenlerin öğretimsel özerkliklerinin artırılması ve bu geniş alanda aldıkları kararlardan sistematik bir biçimde sorumlu olmalarını özendirecek politikalar uygulanmalıdır. Bu politikalar standartlaştırılmış ve test merkezli olmayan esnek ve dengeli hesap verilebilirlik yaklaşımlarını içermelidir.